Pegylated Interferon Mono‐Therapy of Chronic Hepatitis C in the Dialysis Population: Systematic Review and Meta‐Analysis. Issue 6 (21st July 2015) - Fabrizi, Fabrizio; Dixit, Vivek; Messa, Piergiorgio; Martin, Paul
Abstract: The medical literature on mono‐therapy with pegylated interferon for chronic hepatitis C in dialysis patients is mostly based on small clinical studies and the efficacy and safety of such approach is still unclear. A systematic review of the literature with a meta‐analysis of clinical studies was performed in order to evaluate the efficacy and safety of mono‐therapy with pegylated interferon of chronic hepatitis C in patients on regular dialysis. The primary outcome was sustained viral response (as a measure of efficacy); the secondary outcome was drop‐out rate (as a measure of tolerability). The random‐effects model of Der Simonian and Laird was used, with heterogeneity and sensitivity analyses. Twenty‐four clinical studies ( N = 744 unique patients) were retrieved; five (21%) being randomized controlled trials. The summary estimate for sustained viral response and drop‐out rate was 0.40 (95% confidence interval [CI], 0.35; 0.46) and 0.14 (95% CI, 0.09; 0.20), respectively. The most frequent side‐effects requiring discontinuation of treatment were hematological (31/83 = 37%) and gastrointestinal (9/31 = 10.8%). Meta‐regression analysis showed a detrimental role of ageing on the frequency of sustained virological response ( P = 0.01); drop‐out rate was greater in diabetics ( P < 0.005). Important heterogeneity was seen with regard to drop‐out rate only. In summary, pegylated interferon monotherapy of hepatitis C in dialysis patients resulted unsatisfactory in terms of efficacy and safety. Studies with novel direct‐acting antiviral agents in combination with pegylated interferon and ribavirin for the treatment of hepatitis C virus in dialysis population are under way.